Pengaruh Kualitas Produk, Kualitas Layanan Dan Kepercayaan Pelanggan Terhadap Loyalitas (Pelanggan Pada Pelanggan Ijo Ireng Coffee 99 Malang) - Aditya Fachrul Zul Aslam; Muhammad Mansur; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine the effect of Product Quality, Service Quality, and customer trust on customer loyalty Ijo ireng coffee 99 Malang, the sample of this study is consumers of Ijo ireng coffee 99 Malang. For data collection using a questionnaire to consumers in Ijo ireng coffee Malang, to analyze data using validity, reliability, normality, multiple linear analyze test F and statistical tests t, coefficient determination test in IBM Statistical Package for Social Science (SPSS) 16.0 version..From the results of calculations with SPSS that are quality product, quality service and trust customers variables simultaneously and significantly affect customer loyalty. While partially the product quality variable has no effect on customer loyalty. Whereas the variable service quality and customer trust partially have a positive and significant effect on customer loyalty. Keywords: product quality, service quality, customer trust and customer loyalty.